2019
DOI: 10.1021/acs.jafc.9b00087
|View full text |Cite
|
Sign up to set email alerts
|

Defense Responses, Induced by p-Coumaric Acid and Methyl p-Coumarate, of Jujube (Ziziphus jujuba Mill.) Fruit against Black Spot Rot Caused by Alternaria alternata

Abstract: The esterified fraction of jujube (Ziziphus jujuba Mill.) peel extract showed strong antifungal activity on Alternaria alternata. p-Coumaric acid (pCA) was found to be the most predominant individual phenolic acid that was correlated highly with the antifungal activity of the esterified fraction. Thus, effects of postharvest treatments with pCA and its simplest esterified derivative methyl p-coumarate (MeCA) against black spot rot on jujube fruit caused by A. alternata were investigated. pCA and MeCA strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 44 publications
1
41
0
Order By: Relevance
“…For example, the metabolites of caffeic acid including reduction reaction product (M5) and glucuronic acid product (M9), the metabolic pathways of caffeic acid, and the related metabolites were displayed in Figure . It is worth mentioning that most constituents migrating into blood, such as (E)‐p‐coumaric acid and ferulic acid, exhibit various pharmacological activities such as anticancer , antidiabetic , antiobesity , anti‐inflammatory , antiedema , antimicrobial , antihepatotoxic , antioxidative , and other effects . For example, Sharma et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the metabolites of caffeic acid including reduction reaction product (M5) and glucuronic acid product (M9), the metabolic pathways of caffeic acid, and the related metabolites were displayed in Figure . It is worth mentioning that most constituents migrating into blood, such as (E)‐p‐coumaric acid and ferulic acid, exhibit various pharmacological activities such as anticancer , antidiabetic , antiobesity , anti‐inflammatory , antiedema , antimicrobial , antihepatotoxic , antioxidative , and other effects . For example, Sharma et al.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the metabolites of caffeic acid including reduction reaction product (M5) and glucuronic acid product (M9), the metabolic pathways of caffeic acid, and the related metabolites were displayed in Figure 3. It is worth mentioning that most constituents migrating into blood, such as (E)-p-coumaric acid and ferulic acid, exhibit various pharmacological activities such as anticancer [31,32], antidiabetic [33], antiobesity [34], anti-inflammatory [35], antiedema [36], antimicrobial [37], antihepatotoxic [38], antioxidative [39], and other effects [40][41][42]. For example, Sharma et al [32] discussed the effect of (E)-p-coumaric acid on glucose-regulated protein 78 in colon cancer and its impact on unfolded protein response: the result showed that (E)-p-coumaric acid significantly downregulated protein 78 and activated the unfolded protein response, mediated apoptosis in both in vitro and in vivo models of colon cancer, and dramatically reduced inflammation by decreasing the expression levels of cytokines COX-2, IL-6, TNF-α, PGE2, p-p65 and p-IκBα.…”
Section: Chemical Composition Analysis Of Corn Silk Aqueous Extract Imentioning
confidence: 99%
“…Moreover, numerous phenolic acids and phenolic-rich extracts exhibited high inhibitory effects on the radial growth of fungi [18,47]. Although considerable attempts have been made using naturally phenolic-rich products against Alternaria alternata [19][20][21][22][48][49][50][51], very few reports are available about their roles against A. solani. Nevertheless, the physiological and biochemical mechanisms behind this role are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…However, here, the amount of ferulic acid was more important in the banana crown samples than in the root samples. Coumaric acid and its methyl ester possess antifungal properties and increase after infection, being associated with phytoalexin‐like behaviour in many plants (Daayf et al ., 1997; Li et al ., 2018; Yuan et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%